Functioning of Long Noncoding RNAs Expressed in Macrophage in the Development of Atherosclerosis - Ma, Xirui; Liu, Huifang; Chen, Fengling (Frontiers in Pharmacology, 2020)
Chronic inflammation is part of the pathological process during atherosclerosis (AS). Due to the abundance of monocytes/macrophages within the arterial plaque, monocytes/macrophages have become a critical cellular target in AS studies. In recent decades, a number of long noncoding RNAs (lncRNAs) have been found to exert regulatory roles on the macrophage metabolism and macrophage plasticity, consequently promoting or suppressing atherosclerotic inflammation. In this review, we provide a comprehensive overview of lncRNAs in macrophage biology, highlighting the potential role of lncRNAs in AS based on recent findings, with the aim to identify disease biomarkers and future therapeutic interventions for AS.